S-Prime Ideals in Principal Domain - Mohamed Aqalmoun (Journal of the Indonesian Mathematical Society, 2023)
Let R be a commutative ring and S be a multiplicative subset of R. The S-prime ideal is a generalization of the concept of prime ideal. In this paper, we completely determine all S-prime and S-maximal idealsof a principal domain. It is shown that the intersection of any descending chain of S-prime ideals in a principal domain is an S-prime ideal, also the S-radical is investigated.